Fire in the Carboniferous earth system - Andrew C. Scott (Evolving Earth)
The Carboniferous is the first geological Period to experience extensive wildfire. A combination of the diversification of land vegetation and its spread into all major terrestrial settings and the rise in atmospheric oxygen paved the way for the development of significant wildfire occurrence that had a significant impact upon the global Earth system. Here the occurrence and study of Carboniferous charcoal deposits is outlined together with an assessment of the evolution of wildfire systems. The influence of fire on plant distribution is assessed. The impact that wildfire had an impact on terrestrial sedimentary systems is described with examples of post-fire erosion and deposition. The wider redistribution of phosphorous in both terrestrial and marine systems is also considered and it is suggested that such events may have played a role in the formation of black shales both in the lacustrine and the marine environment. The role of fire in relation to the evolution of several plant traits is discussed and it is concluded that at least three – the dropping of coniferous lower branches, the shedding of lycopsid leaves from the trunks of arborescent forms and the development of extensive bark and periderm in a range of plants have some merit. Equally the rise of the liana habit, especially in the pteridosperms may also have had an impact in the spread of wildfires in the Pennsylvanian. It is suggested that the role of wildfire (that today is so important and significant) be considered by geologists and palaeonotologists not only concerned with the evolution of the Carboniferous earth system but also in the Earth system from at least the early Silurian and throughout the rest of the Phanerozoic.